Defining the role of neoadjuvant systemic therapy in high‐risk retroperitoneal sarcoma: A multi‐institutional study from the Transatlantic Australasian Retroperitoneal Sarcoma Working Group. Issue 5 (18th November 2020) - Tseng, William W.; Barretta, Francesco; Conti, Lorenzo; Grignani, Giovanni; Tolomeo, Francesco; Albertsmeier, Markus; Angele, Martin K.; Rutkowski, Piotr; Skoczylas, Jacek; De Paoli, Antonino; Navarria, Federico; Raut, Chandrajit P.; et al.
Abstract : Background: In patients with retroperitoneal sarcoma (RPS), the incidence of recurrence after surgery remains high. Novel treatment approaches are needed. This retrospective study evaluated patients with primary, high‐risk RPS who received neoadjuvant systemic therapy followed by surgery to 1) determine the frequency and potential predictors of radiologic tumor responses and 2) assess clinical outcomes. Methods: Clinicopathologic data were collected for eligible patients treated at 13 sarcoma referral centers from 2008 to 2018. Univariable and multivariable logistic models were performed to assess the association between clinical predictors and response. Overall survival (OS) and crude cumulative incidences of local recurrence and distant metastasis were compared. Results: Data on 158 patients were analyzed. A median of 3 cycles of neoadjuvant systemic therapy (interquartile range, 2‐4 cycles) were given. The regimens were mostly anthracycline based; however, there was significant heterogeneity. No patients demonstrated a complete response, 37 (23%) demonstrated a partial response (PR), 88 (56%) demonstrated stable disease, and 33 (21%) demonstrated progressive disease (PD) according to the Response Evaluation Criteria in Solid Tumors, version 1.1. Only a higher number of cycles given was positively associated with PR ( P  = .005). All patients underwent complete resection, regardless of the tumor response. Overall, patients whose tumors demonstrated PD before surgery showed markedly worse OS ( P  = .005). An indication of a better clinical outcome was seen in specific regimens given for grade 3 dedifferentiated liposarcoma and leiomyosarcoma. Conclusions: In patients with high‐risk RPS, the response to neoadjuvant systemic therapy is fair overall. Disease progression on therapy may be used to predict survival after surgery. Subtype‐specific regimens should be further validated. Abstract : In patients with retroperitoneal sarcoma, the response to neoadjuvant systemic therapy is fair overall. An indication of a better clinical outcome is seen with histologic subtype–specific regimens.